THE STRATEGIC PLANNING PROCESS IN DEVELOPING QUALITY ISLAMIC EDUCATION - Al-Mursal, Nurul Mawaddah (BiCED Proceeding, 2024)
This study adopts a library research approach to examine the process of strategic planning in Islamic education, with a focus on strategies for building quality education. The strategic planning process in Islamic education involves internal and external environmental analysis, the setting of short-term and long-term goals, and the development of strategies that are relevant to the times. This research outlines the steps of strategic planning, ranging from environmental analysis, goal setting, strategy formulation, to evaluation and control. Furthermore, this study discusses the importance of improving human resource quality, a curriculum based on the needs of the times, the utilization of technology, and a holistic approach to Islamic education that encompasses intellectual, moral, spiritual, and social aspects. Thus, this research provides guidance on how Islamic educational institutions can formulate and implement strategic planning to achieve quality education goals that are relevant to societal demands and in alignment with Islamic values